Adolescents’ identity development through literature: A study of pedagogy and canon in the Grade 11 English FAL poetry classroom - Mavhiza, Grace (University of the Witwatersrand, Johannesburg, 2023)
The aim of this study was to analyse the effect of pedagogy and canon on adolescents’ identity development in the Grade 11 English First Additional Language (FAL) poetry classroom. Despite the well-documented benefits of poetry (Femer, 2003; Pushpa & Savaedi, 2014; Antika, 2017), this study identified the problem that poetry is not realising its potential as a subject in the schools in relation to the identity development of adolescents. The school is a place where adolescents spend much of their time and there are many factors which shape adolescents’ identities within the school context. This qualitative study focused on pedagogy and canon among these many factors. The study was designed as a dual case study and set up within the interpretivism paradigm which allowed different interpretations of the data about the effect of pedagogy and canon on adolescents’ development. The complexity of the study meant a dual focused theoretical framework. Thus, the study used a combination of the theories of identity development by Erik Erikson (1963; 1968) and critical pedagogy by Paulo Freire (1970). Purposive sampling was used to identify the cases for this study. The two schools selected happen to be within Ekurhuleni District. In one school the teacher applied traditional pedagogy while in the other school the teacher employed the modern pedagogy which included multimodality, multiliteracies and new literacies. Qualitative data was collected using three tools, namely, participant observation, questionnaire, and reflective journals. Descriptive and thematic analyses of data were conducted, and the results show that there are limitations and affordances of both the traditional and modern pedagogies. In relation to the impact of the poetry pedagogy and canon on adolescents’ identity development in the Grade 11 English FAL poetry classroom, key findings reveal that traditional pedagogy takes away adolescents’ opportunities to explore their personal identities. In addition, the modern pedagogy is preferable among the Grade 11 English FAL poetry adolescents who participated in this study. The study concluded that the current Grade 11 English FAL poetry canon is alienated from the lives of adolescents who participated in this research. Learners yearn for new poetry which speaks to their daily experiences.
The thesis is being submitted in fulfilment of the requirements for the degree of a PhD, top the Faculty of Humanities, in the Wits School of Education, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Adolescents; Identity; Pedagogy; Canon; Multimodality; Multiliteracies; UCTD; SDG-4: Quality education